General d’Arblay’s Mementoes of a Military Life - Al Jamil, Miriam (The Burney Journal, 2025)
Later in life, General Alexandre d’Arblay became acutely aware that his wife’s literary fame might eclipse his own military honors in the eyes of posterity, and he became anxious that his son Alex should have some evidence of his achievements after his death. His trip to Paris in 1817 was made in part to have a portrait painted by Horace Vernet to commemorate his military status. This article examines the portrait, alongside a panoramic sketch of the field of Waterloo that d’Arblay made, to argue that the production and curation of these military mementoes were originally intended to fashion a legacy of his achievements, independent of his wife’s literary fame, for the benefit of his son.